2020
DOI: 10.1002/cctc.202000205
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Esterification of 5‐Hydroxymethylfurfural under Flow Conditions Using a Bimetallic Co/Ru Catalyst

Abstract: Furanic di‐carboxylate derivatives of 5‐Hydroxymethylfurfural (HMF) are nowadays important in the polymer industry as they are used as building blocks for bio‐based polyesters. The high reactivity of HMF compels to avoid harsh synthetic conditions. Therefore, developing mild catalytic processes for its selective oxidation is a challenging task. Herein, we report the first oxidative esterification of HMF to dimethyl furan‐2,5‐dicarboxylate (FDCM) under flow conditions using oxygen as oxidant. For that purpose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A bimetallic catalyst mixture of the Co x O y -N + RuO x N support on C-irregular or C-pellets nanoparticles (C-irregular shape with −20 + 40 mesh and cylindrical pellets with ∼0.8 mm diameter) has been investigated for the oxidative esterification of HMF in a flow regime. 78 98% HMF conversion and 57% FDMC yield were obtained using Co x O y -N + RuO x N@C-irregular as the catalyst. In comparison with the batch result (0.03 mmol h −1 ), more than 15-fold increase of FDMC production (0.47 mmol h −1 ) was obtained in the flow regime.…”
Section: Hmf Oxidative Esterification To Fdmc Under a Continuous Flowmentioning
confidence: 99%
“…A bimetallic catalyst mixture of the Co x O y -N + RuO x N support on C-irregular or C-pellets nanoparticles (C-irregular shape with −20 + 40 mesh and cylindrical pellets with ∼0.8 mm diameter) has been investigated for the oxidative esterification of HMF in a flow regime. 78 98% HMF conversion and 57% FDMC yield were obtained using Co x O y -N + RuO x N@C-irregular as the catalyst. In comparison with the batch result (0.03 mmol h −1 ), more than 15-fold increase of FDMC production (0.47 mmol h −1 ) was obtained in the flow regime.…”
Section: Hmf Oxidative Esterification To Fdmc Under a Continuous Flowmentioning
confidence: 99%
“…E. Mejı ´a et al reported the oxidative esterification of HMF in a flow regime with excellent conversion and good selectivity using a Co x O y -N + RuO x -N@C-irregular catalyst. [12][13][14][15] Notably, most of the known catalyst systems for the esterification of aromatic alcohols under mild conditions are based on noble metals such as Au, Pd and Ru. 6,[16][17][18][19][20][21] Due to the natural scarcity and high price of noble metals, it is extremely important to develop non-noble metal-based catalysts as alternatives to traditional noble metal catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Microreactor operation allows a precise temperature control of such (aerobic) oxidation reactions and enhances safety (additionally due to low inventory and explosion suppression e.g., when using pure O 2 ) [72]. Very recently, the aerobic oxidation of HMF over heterogeneous catalysts has received research attentions in microreactors [73][74][75][76]. A wall-coated tube-in-tube polytetrafluoroethylene (PTFE) microreactor was used for the oxidation of HMF to DFF in dimethyl sulfoxide (DMSO) over a salen-transition metal core-shell (Fe 3 O 4 /SiO 2 /Mn) catalyst [74].…”
Section: Introductionmentioning
confidence: 99%
“…35% FDCA, which resulted in crystal formation due to the low solubility of FDCA in the solvent. Also, the oxidative esterification of HMF and methanol to FDCM using oxygen as the oxidant benefitted from operation in a packed bed microreactor with nitrogen-doped carbon-supported bimetallic Co/Ru as the solid catalyst [76]. In the microreactor the FDCM production rate was found over 15-fold higher than in batch reactors [76].…”
Section: Introductionmentioning
confidence: 99%